ANALYSIS OF COOPERATIVE HEALTH LEVEL ON KOPWAN MEKAR KENANGA TULUNGAGUNG YEAR 2019 – 2021 - M Marlena; E Widhajati; Henny Rakhmawati; Ersi Setyo Fitriani (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
This study aims to determine the health status of Kopuwan Mekar Kenanga in the fiscal year 2019-2021 based on Decree No. 14/Per/M of the Minister for Cooperatives and SMEs, Republic of Indonesia. His KUKM on Guidelines for Assessing the Health of Savings and Loan Cooperatives and Savings and Loan Cooperatives arising from aspects of Capital, Quality of Produced Assets, Management, Liquidity, Efficiency, Independence and Growth, and Cooperative Identity /XII/2009. The research method used is quantitative research and uses descriptive data analysis. As a result of the analysis, the health level of Kopwan Mekar Kenanga indicates that the health level in 2019 and 2020 is a fairly healthy predicate, and the low score in 2020 indicates that the condition is fluctuating from 2019 to 2021. is showing. However, in 2021, Kopwan Mekar Kenanga earned the title of health as his health level increased along with the significant increase in his score.